Litigants Instruction, of Antonio de Paz y Salgado:an alternative non-judicial model to resolve conflicts - López-Murcia, Rafael Antonio (Universidad Pedagógica y Tecnológica de Colombia, 2014)
This is an interesting historical exploration that reveals how a recently discovered text of the seventeenth century already talked of “non-judicial methods” to resolve conflicts, through amicable settlement. The wise advice in such ancient times shows a great wisdom that reminds us the popular adage: “Better a bad deal, than a good lawsuit”. The author is currently a judge in Tegucigalpa.